The Word in Celebration. Vol. 1: Prayerful Study and Reflection on the Biblical Readings in the Sacred Liturgy of the Passion Week and the Great Sunday of Resurrection in the Syriac Tradition - Kochappilly, Paulachan (Asian Horizons, 2011)
George Kaniarakath, CMI & Varghese Pathikulangara, CMI, The Word in Celebration. Vol. 1. Prayerful Study and Reflection on the Biblical Readings in the Sacred Liturgy of the Passion Week and the Great Sunday of Resurrection in the Syriac Tradition, Kottayam: Denha Services, 2011. Pages: 147+8. ISBN 978-81-905799-9-5